Squares : urban spaces in Europe - Wolfrum, Sophie (Birkhäuser, 2015)
The question of spatial composition and user quality of sites arises in every urban design concept or intervention in urban public spaces. Squares is the first wide-ranging reference work in which the design and proportions of urban squares are compared and studied. Seventy European public squares are presented systematically in as-built plan, ground plan, section, and axonometric projection with the most important characteristics.